Does Profit Maximization Assumption in Economics Comply with Shariah? Evidence from Theoretical and Empirical Findings - Sunaryati Sunaryati; Abdul Qoyum (Global Review of Islamic Economics and Business, 2022)
The objective of this paper is to discuss the issue of profit maximization from a shariah point of view. The study is very relevant, especially in the current development of Islamic economics. Profit maximization is the central issue in conventional economics and the implication is that all firm decisions must be intended to realize a profit. This paper uses a qualitative approach to answer the main research question. Using a comprehensive study on the Al-Quran and previous empirical findings, the study reveals that profit maximization is still accepted, but not as a single objective. Islamic economics must use comprehensive objectives that not only profit but also maqasid shariah maximization, including environmental, and social aspects.